2007
DOI: 10.1038/nature06104
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-striatal synaptic defects and OCD-like behaviours in Sapap3-mutant mice

Abstract: Obsessive-compulsive disorder (OCD) is an anxiety-spectrum disorder characterized by persistent intrusive thoughts (obsessions) and repetitive actions (compulsions). Dysfunction of cortico-striatothalamo-cortical circuitry is implicated in OCD, though the underlying pathogenic mechanisms are unknown. SAP90/PSD95-associated protein 3 (SAPAP3) is a postsynaptic scaffolding protein at excitatory synapses that is highly expressed in the striatum. Here we show that mice with genetic deletion of SAPAP3 exhibit incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
818
5
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 727 publications
(897 citation statements)
references
References 50 publications
(7 reference statements)
51
818
5
8
Order By: Relevance
“…Given the finding of increased anxiety‐like behavior in postpartum HFD dams, it is possible that this excessive self‐grooming represents a repetitive, anxious phenotype (Shmelkov et al., 2010; Welch et al., 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the finding of increased anxiety‐like behavior in postpartum HFD dams, it is possible that this excessive self‐grooming represents a repetitive, anxious phenotype (Shmelkov et al., 2010; Welch et al., 2007). …”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that HFD may be protective against depressive‐like behavior, although future studies are needed to confirm this hypothesis. Excessive self‐grooming, observed in HFD dams, is one of the hallmark symptoms in an OCD mouse model, which is also associated with increased anxiety‐like behaviors (Shmelkov et al., 2010; Welch et al., 2007). Notably, studies in humans have found that up to one third of women report obsessive‐compulsive behaviors in the early postpartum period, often in association with negative maternal mood (Miller, Hoxha, Wisner, & Gossett, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological grooming behavior has been hypothesized to be related to obsessive-compulsive disorder (OCD)-in humans and other animals-in terms of phenomenology and possible selective response to serotonergic drugs Rapoport et al, 1992;Bordnick et al, 1994;Overall and Dunham, 2002;Graf et al, 2003; but also see Bloch et al, 2007], and this behavior in Sapap3 mutant mice led Welch et al to perform a set of experiments testing the extent to which these mouse behaviors resemble OCD in humans. The Sapap3 mutant mice showed increased anxiety-like behavior in open field, dark-to-light emergence, and elevated zero maze tests, and 6-day fluoxetine treatment of these mice reduced both excessive grooming and anxiety-like behaviors [Welch et al, 2007]. Cortico-striatal circuits appear dysfunctional in persons with OCD [Graybiel and Rauch, 2000;Saxena and Rauch, 2000;Aouizerate et al, 2004;Swedo and Snider, 2004;Menzies et al, 2007]; thus, it is highly relevant that Sapap3 mutant mice also showed defects in cortico-striatal synapses in electrophysiological, biochemical, and structural studies.…”
Section: Introductionmentioning
confidence: 97%
“…There are four highly homologous members of the SAPAP family, and a recent study found that mice with a deletion of the Sapap3 gene groom themselves excessively [Welch et al, 2007]. This grooming behavior appears similar in nature to that of wild-type mice but is much more frequent, leading to facial hair and skin removal in the absence of peripheral cutaneous defects [Welch et al, 2007].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation